Mi vida es un tango - Historia de vida - Acevedo Muñoz, Claudia Liliana (Universidad Antonio Nariño, 2021)
This research arose out of the interest of making my career professional artistic - pedagogical that for more than 30 years I have nurtured in dance, especially in the tango genre, an invitation made by the Antonio Nariño University. And the modality of work that I consider pertinent to approach this degree work is "The Artistic Experience Pedagogical to the Present State of the Tradition ”modality that allows to go approaching the history from my parents, going through my tutors, colleagues and institutions that influenced me learning and teaching fragmenting emotional experiences and professional experiences in an experiential account. Therefore, the qualitative approach is approached, and the techniques implemented to collect this information: they were the semi-structured interview and unpublished experiential material